2014
DOI: 10.1007/s11916-014-0461-0
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome and Pain Disorders: What’s in common?

Abstract: Between 10 % and 30 % of the population report chronic pain. More than half of these also have sleep complaints. From considering these data, it can be inferred there is a significant overlapping between these conditions. Restless Legs Syndrome/Willis-Ekbom Disease (RLS/WED) is characterized by complaints of an "urge to move" frequently associated with dysesthesias. From that perspective, these sensations can also have painful characteristics. By the same token, the presence of comorbid diseases as predicted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 95 publications
(96 reference statements)
0
9
0
Order By: Relevance
“…The medial thalamic nuclei are part of the limbic system, which is modulated by dopaminergic afferents. Another study found thalamic activity changes in the thalamocotrical circuit ( Goulart et al, 2014 ). Therefore, it was hypothesized that the dopaminergic dysfunction might lead to an impairment of the medial pain system ( Garcia-Borreguero and Williams, 2014 ; Goulart et al, 2014 ) and then caused the uncomfortable symptoms of RLS.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The medial thalamic nuclei are part of the limbic system, which is modulated by dopaminergic afferents. Another study found thalamic activity changes in the thalamocotrical circuit ( Goulart et al, 2014 ). Therefore, it was hypothesized that the dopaminergic dysfunction might lead to an impairment of the medial pain system ( Garcia-Borreguero and Williams, 2014 ; Goulart et al, 2014 ) and then caused the uncomfortable symptoms of RLS.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Notably, RLS correlates best with PLM-associated arousals rather than PLM severity 75,76 consistent with the relationship of this disorder to sleep fragmentation and deprivation. 28 Second, the morphology of basal nuclei revealed no gross abnormalities in structure, no degenerative features, and quite stable dopamine activities in patients with RLS. 77 Severity of both RLS and PLM relate to higher g-aminobutyric acid levels in the thalamus and lower levels in the cerebellum, as determined by localized magnetic resonance spectoscopy.…”
Section: Interpretation Of the Proposed Mechanismmentioning
confidence: 84%
“…9 The association of RLS with sleep deprivation and/or fragmentation may be caused by reduction in pain thresholds, modulated by a variety of neurotransmitters, particularly dysfunction of monoaminergic circuits. 28 The association of RLS with autoimmune disorders has been long recognized 29 with significant comorbidity of inflammation, intestinal bacterial overgrowth, iron deficiency, and peripheral neuropathy, suggesting an immunologic basis of secondary RLS. 30 Some studies found elevated inflammatory cytokines, most prominent interleukin-6 and tumor necrosis factor-a, 30 although other studies failed to observe such a correlation.…”
Section: Associated Disordersmentioning
confidence: 99%
“…There is a sizeable population of chronic pain patients who suffer from comorbid RLS [11], as did the patients described here. Because spinal cord stimulators are already implanted with relative ease and adjustment to include areas involved in RLS is not difficult or dangerous, using SCS to target chronic pain in these patients thus also grants the additional opportunity to provide potential ancillary RLS treatment to many people.…”
Section: Discussionmentioning
confidence: 99%